Mitigation of order-effects on investment decision making - Auravita Astania; Luciana Spica Almilia (Universitas Hayam Wuruk Perbanas, 2016)
This study attests the belief-adjustment model to examine whether there are differences in investment decision making between the participants who obtain good news fol-lowed by bad news and those who obtain bad news followed by good news on the in-formation pattern which is processed based on end-of-sequence and long series infor-mation. The experiment design in this study is the pattern of presentation 1x1x2 end-of-Sequence, a long series information and directions of evidence (good news followed by bad news and bad news followed by good news). The research hypotheses were tested using Mann Whitney test. The variables used in this research are investment decision, pattern of presentation in end-of-sequence, length of the series of information, and order of evidence. The participants involved in this research are 47 students (ba-chelor program) of STIE Perbanas Surabaya majoring in Accounting and Manage-ment who are taking or have taken courses of Financial Statement Analysis and/or Investment Management and Capital Markets. The results show that there is no sig-nificant difference in the judgment between the participants who obtain good news followed by bad news and those who obtain bad news followed by good news. In addi-tion, there is no order-effect occurring in investment decision making.